Dinâmica da paisagem da Zona de Amortecimento do Parque Estadual de Porto Ferreira como subsídio para a revisão do plano de manejo - Moraes, Mayra Cristina Prado de (Universidade Federal de São Carlos, 2013)
The replacement of natural habitats by cultures promotes the remaining forest s fragments reduction, they become small, highly disturbed and isolated. The Buffer Zones (BZ) were created on the Conservation Units (CU) surroundings to lessen the adverse impacts exerted by the external environment to them. The main objectives of this study were to analyze the dynamic of the land use change in its anthropic and natural contexts, during the 1971, 1988 and 2008 years; determine the conflicts presents on the Riparian Forest (RF) and understand the processes that occurred in the Buffer Zone of the State Park of Porto Ferreira (SPPF). We conducted a mapping of the study area on Geographic Information Systems (GIS) platform, defining the classes of land s use and occupation. With the aid of landscape metrics (PROX, SHAPE, NNDist, Area, Core Area) was possible to evaluate the fragments in all years of the study. According to the results of the class use, sugarcane was the one that stood out, with a growth of 38.75 % increase over the years, with the largest increase (27.55 %) for the period 1971 -1988. Analyzing the entire period studied, the forested areas, had a reduction of 4.34% in the landscape, which corresponds to 259.7 ha, the fragments became less frequent in the landscape and generally associated with watercourses. For the metric connectivity, there was a tendency to slightly over 50 % of the fragments in the three years studied are not connected with any other. To SHAPE was not observed fragments with rounded shapes for any year, the core area found to forest fragments had 764.83 ha to 1971; 361.75 ha to 1988 ha and 428,21 for the 2008 year . The RF totaled 386 ha, with 39 % natural vegetation present. For the legal scenario, if all the PPA were preserved there would be an increase of 239 ha of natural vegetation. It was found that the dynamics of the use and occupation of the SPPF s BF was governed by economic cycles, and currently it has a matrix with predominance of sugarcane monoculture. The low percentage of natural vegetation, isolation of fragments and lack of greetings legislation with respect to RF in the BZ, are probably contributing to the degradation of the park. It is necessary to propose measures to ensure the sustainability of the landscape.
Keywords: política ambiental; biodiversidade - conservação; parques; métricas da paisagem; planejamento ambiental; Sistemas de Informação Geográfica; landscape metrics; environmental planning; Geographic Information Systems; fragmentation; CIENCIAS BIOLOGICAS